Publications of the Mesoamerican Journal of Agronomy during the period 1990-2010: Classification, thematic, countries and diffusion. - Peña-Navarro, Nelson (2011)
The objective of thisstudy was to assess the thematic and sources of the publicationsin the Me soamerican Journal of Agronomy during theperiod 1990-2010. Mesoamerican Journal of Agronomywas created as a publication of the Ce ntral AmericanCooperative Program for the Improvement of Crops andLivestock (PCCMCA ). From 1990 to date, 629 pape rs havebeen published, of which 63% are scientific articles, 26% aretechnical notes, 8% are analyses and commentarie s, whiletechnical information and literature reviews are 2% each.Costa Rica and Me xico are the countrie s with the largestnumber of published pape rs, with 37 and 32% respectively,followed by El Salvador, Guatemala, Honduras and Cuba.The principa l topics have been corn (24%) and beans (21%),forages (7%), and dairy cattle (4%), while rice, sorghum,weeds and pea ch palm reached 3% each. In 2010, the journalrejected 20% of all pape rs submitted for publication. Wehighlight the distribution of the printed journal to librarie sand documentation centers in thirty countrie s around theworld, mainly the continents of America, Europa, Asia andsome Caribbean islands.